The Influence of Core Values and Organizational Culture on Employees’ Productivity - Inasoria, Romeo (Future Science / FSH-PH Publications, 2025)
An organization can leverage the collective strength of its core values and culture to create a high-performing work environment. It aims to determine the role of core values, organizational culture, and employees’ productivity and understand how these factors enhance the organizational performance of Bulacan State University, Philippines. It utilized a descriptive correlational type of research. The respondents of the study are 357 non-academic employees of the university. The study is limited to non-academic employees in the main campus of Bulacan State University. It likewise utilized validated instruments to measure the core values and organizational culture. The statistical analysis demonstrates that knowledge of the university's core values significantly affects employees’ productivity. The moderately strong correlation and the significant regression coefficient indicate that employees with a better understanding of core values tend to perform better. As regards organizational culture and employee productivity, statistical analysis demonstrates that organizational culture significantly positively affects employees’ productivity. Lastly, the result analysis revealed strong positive correlations between core values, organizational culture dimensions, and employee productivity. Despite the fact that the regression analysis did not reveal any statistically significant effects for individual predictors, the practical implications are still vital. Facilitating the consistent reinforcement and clear communication of fundamental values is imperative for leaders to ensure that they are in accordance with organizational culture. This alignment, although not statistically confirmed in this sample, is widely supported in leadership literature as a factor in the overall performance of an organization, employee engagement, and cohesion.